Hubungan antara Pemberian ASI Eksklusif dengan Status Gizi Pada Bayi Uisa 6-12 Bulan di Desa Kesambirampak Kecamatan Kapongan Kabupaten Situbondo - Dwi Anggun Lestari (Universitas Islam Jember, 2018)
ASI exclusive gift ASI (mother milk water) more beginning may be after birth, given without time-table and is not given food other, although only plain water, until aged baby 6 months. During gift ASI exclusive baby not supposed get liquid addition other milky formula, orange juice, tea water, honey, plain water. the low nutrient status target achievement in age baby 6-12 month in Kesambirampak Village of Sub district of Kapongan of Regency of Situbondo year 2018 is caused the low gift ASI exclusive and will evoke impact that is will retard physical growth, way of thinking development and child intelligence. Method that used in this watchfulness based on watchfulness scope (watchfulness inferential), watchfulness place (field watchfulness), data collecting manner (survey, there/not there treatment (expost facto), data collecting time (cross sectional), plan from this research (analytic corelational), and based on data source (primary watchfulness). Sample taking in this watchfulness uses non probability sampling with technique accidental sampling. Variable in watchfulness that is independent variable in this watchfulness gift ASI exclusive and variable dependent in this watchfulness nutrient status. Instrument that used kuesioner closed by using checklist. Based on watchfulness result in 42 respondents in this watchfulness is that is 19 babies (45,2%) is given ASI exclusive and got 19 babies (45,2%) has good nutrient status and 23 babies (54.8%) is not given ASI exclusive got 21 babies (50,0%) has nutrient status less. by using SPSS correlation test rank biserial with (?)=0,05, got asymp. Sig= 0,000 so, asymp. sig < 0,05. calculation result that is h0 aversed (there connection) Inferential that gift ASI exclusive has connection with nutrient status in Kesambirampak Village of Sub district of Kapongan of Regency of Situbondo. On that account, well being energy must can in crease service quality so that nutrient status scope can be increased.